Сyclotron wave absorption in D-shaped tokamaks - Grishanov, N.I.; Azarenkov, N.A. (Вопросы атомной науки и техники, 2016)
Transverse dielectric susceptibility elements are derived for radio-frequency waves in a large aspect ratio toroidal
plasma with D-shaped magnetic surfaces by solving the Vlasov equation for untrapped and usual t-trapped particles
under moderate elongation and small triangularity in the case, when the so-called d-trapped particles are absent.
These dielectric characteristics are suitable for estimating the wave dissipation by the fundamental cyclotron
resonance damping in the frequency range of ion-cyclotron and electron cyclotron resonances. Поперечные элементы диэлектрической восприимчивости для радиочастотных волн в плазме аксиально-
симметричных токамаков с большим аспектным отношением, умеренной эллиптичностью и малой
треугольностью магнитных поверхностей D-образного сечения получены на основании решения уравнений
Власова для пролётных и t-запертых частиц в случае, когда так называемые d-запертые частицы
отсутствуют. Эти диэлектрические характеристики применимы для оценки циклотронного поглощения
электромагнитных волн (например, во время нагрева плазмы) в диапазоне частот ионно-циклотронного или
электронно-циклотронного резонансов. Поперечні елементи діелектричної сприйнятливості для радіочастотних хвиль в аксіально-симетричних
токамаках з великим аспектним співвідношенням, помірної еліптичностью та малої трикутностью магнітних
поверхонь D-подібного перерізу отримані через розв'язок рівнянь Власова для пролітних та t-запертих
частинок в умовах коли так званні d-заперті частинки відсутні. Ці діелектричні характеристики мають бути
застосовані для оцінки циклотронного поглинання електромагнітних хвиль (наприклад, під час нагріву
плазми) у діапазоні частот іонно-циклотронного або електронно-циклотронного резонансів.